Grains of knowledge: Genomics of model cereals - Paterson, Andrew H.; Freeling, Michael; Sasaki, Takuji (Genome Research, 2005)
The economic and scientific importance of the cereals has motivated a rich history of research into their genetics, development, and evolution. The nearly completed sequence of the rice genome is emblematic of a transition to high-throughput genomics and computational biology that has also pervaded study of many other cereals. The relatively close (ca. <50 million years old) relationships among morphologically diverse cereals native to environments that sample much of global geographic diversity make the cereals particularly attractive for comparative studies of plant genome evolution. Extensive germplasm resources, largely a byproduct of their economic importance, together with growing collections of defined mutants, provide foundations for a host of post-genomic studies to shed more light on the relationship between sequence and function in this important group. Using the rapidly growing capabilities of several informatics resources, genomic data from model cereals are likely to be leveraged tremendously in the study and improvement of a wide range of crop plants that sustain much of the world's population, including many which still lack primary genomic resources.
10.1101/gr.3725905